Research on the Cultivation of Skilled Workers in the Era of "Internet+" - Liu, Dongxuan (Journal of Theory and Practice of Social Science, 2023)
As the foundation for cultivating a new generation of information technology talents, the development level of vocational education directly affects the optimization and upgrading of professional skills and quality structures in China's future information technology industry, software industry, and manufacturing industry. Based on the "Internet plus" era, this paper studies the direction of innovation and entrepreneurship curriculum reform in technical colleges. Exploring the problems and reasons in the path of vocational ability cultivation for vocational college students in the new situation, in order to promote vocational education to better adapt to social needs; At the same time, suggestions and strategies are proposed to improve the efficiency of vocational practice, reduce costs, and improve teaching content through the improvement of traditional teaching models.